في أسباب تغير دلالات الألفاظ - مساعدية, لزهر (جامعة الوادي - University of Eloued, 2020)
إن اللغة ظاهرة اجتماعية، وهي شبيهة بالكائن الحي فهي تحيا في أحضان المجتمع، وتتطور بتطوره، فترقى برقيه، وتنحط بانحطاطه. فكما يتطور الكائن الحي ويتغير، تتطور، و كما ينمو تنمو. فمعاني الألفاظ لا تستقر على حال، بل هي في تغير دائم ،ومرد ذلك إلى عوامل مختلفة. لذلك سوف تسعى هذه الورقة البحثية إلى محاولة تبين أهم عوامل التغير الدلالي. الكلمات المفتاحية: اللغة . الظاهرة. الدلالة .التغير. المجتمع. Abstract: The Language is a social phenomenon, which is similar to the living organism, it lives in the arms of society, and evolves with its development, so that it promotes its telegram and degenerates. As an organism evolves and changes, it evolves, and as it grows it grows. The meanings of words do not stabilize anyway, but are constantly changing, due to various factors. Therefore, this paper will seek to try to identify the most important factors of semantic change. key words: The language . Phenomenon. Change. Semantics. the society.
In The Reasons For The Change Of Semantics.
مقال
Keywords: اللغة . الظاهرة. الدلالة .التغير. المجتمع.; The language . Phenomenon. Change. Semantics. the society.